Analysis of the Alignment Between the Curriculum Structure of the Arabic Language Education Department and the Needs of Graduates: تحليل توافق البنية المنهجية لقسم تعليم اللغة العربية مع احتياجات الخريجين - Ahmad Sirojuddin Syarif; Hanik Mahliatussikah; Moh. Khasairi; Ibnu Samsul Huda (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to analyze the alignment of the curriculum structure in the Arabic Language Education study program at UIN Syarif Hidayatullah Jakarta with the competency needs of graduates that are relevant to the workforce and the advancement of scientific knowledge. The method used is qualitative descriptive with a document study approach, through the analysis of curriculum documents and Course Learning Outcomes. The results indicate that the curriculum has been systematically and structurally organized into four groups of courses: General Courses, Basic Educational Courses, Educational Expertise Courses of the Study Program, and Study Program Courses. The alignment between course learning outcomes and the curriculum in the domains of attitudes, knowledge, and skills has been fulfilled through various relevant courses, enabling the formation of graduates who not only possess knowledge and skills but also professional attitudes and strong character. This study recommends that curriculum development continues to be adjusted to the dynamic developments of science, technology, and labor market needs so that graduates can compete and contribute optimally.